2021
DOI: 10.21037/gs-20-775
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcomes of lipofilling in breast reconstruction: a matched cohort study with 250 patients

Abstract: Background: Fat grafting is a procedure commonly used in breast reconstruction nowadays. Nevertheless, its oncological safety remains controversial. The potential risk that progenitor cells included in fat graft tissue may contribute to disease progression in patients with breast cancer is still debatable. We have designed a matchingcohort study with 250 patients with history of breast cancer trying to elucidate an answer for this question.Methods: We selected 250 patients with a history of breast cancer in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Studies have widely demonstrated the oncologic safety of fat grafting for breast reconstruction [5][6][7]44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have widely demonstrated the oncologic safety of fat grafting for breast reconstruction [5][6][7]44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Although initial skepticism has surrounded the oncological safety of fat grafting in breast reconstruction, studies found strong evidence demonstrating no increase in breast cancer recurrence or mortality [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Some included small population samples, which makes the interpretation of their results difficult. 35,37,38 Other articles focused solely on specific tumor characteristics or specific breast reconstruction procedures. For instance, Myckatyn et al focused only on invasive ductal cancer cases, and their patient population mostly included implant-based breast reconstruction, 39 whereas Masia et al 40 and Fertsch et al 41 focused only on free-flap–based breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tissue modeling can be specific for each patient’s anatomic features, such as the thorax width, the contralateral breast volume, or the desired volume in case of bilateral mastectomies and the overall appearance. However, donor site outcomes, surgery duration and safety concerns have emerged regarding the risk of cancer recurrences due to growth factors within the fat graft and the postoperative calcifications ( 12 ).…”
Section: Introductionmentioning
confidence: 99%